PENGARUH PROACTIVE PERSONALITY DAN WORK SOCIAL SUPPORT TERHADAP TURNOVER INTENTION DENGAN CAREER ADAPTABILITY SEBAGAI VARIABEL MEDIASI PADA KARYAWAN BARU DI INDUSTRI PERHOTELAN DI DAERAH ISTIMEWA YOGYAKARTA - Betina Noor Faidah Zamzam; Ristianawati Dwi Utami (Journal Economics Technology And Entrepreneur, 2026)
This study aims to examine the effects of proactive personality and work social support on turnover intention, with career adaptability as a mediating variable among newly hired employees in the hospitality industry in the Special Region of Yogyakarta. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. The analysis encompassed the evaluation of the measurement model, structural model, and mediation effects. The findings indicate that proactive personality has a positive but non-significant effect on turnover intention, while it exerts a positive and significant influence on career adaptability. Similarly, work social support demonstrates a positive but non-significant relationship with turnover intention, yet significantly enhances career adaptability. Furthermore, career adaptability exhibits a negative but non-significant effect on turnover intention. Mediation analysis reveals that career adaptability does not significantly mediate the relationships between proactive personality and turnover intention, nor between work social support and turnover intention. These results suggest that, among newly employed workers in the hospitality sector, career adaptability has not yet emerged as a decisive factor in determining employees’ intentions to remain with or leave the organization. Consequently, other factors beyond the proposed research model are likely to play a more substantial role in shaping turnover intention.